Precursor B-Cell Lymphoblastic Leukemia-Lymphoma with severe eosinophilia, in a young adult patient - Tello-Vera, Stalin (2020)
Introduction: Acute lymphoblastic leukemia (ALL) of B cells, is the most common subtype of ALL in children.(1,2) ALL that presents as hypereosinophilia in peripheral blood, is very rare and the incidence is <1%.(3) Case Report: In this case, is presented a girl, 25 year old girl, initially diagnosed as community acquired pneumonia and leukemoid reaction with hypereosinophilia. Wich subsequently re-enters with respiratory distress, also finding double moderate mitral injury, moderate tricuspid insufficiency, mild pulmonary hypertension and mild pericardium effusion; finally, a definitive diagnosis of acute lymphoblastic leukemia B with the help of auxiliary examinations.